Understanding the Link Between Consanguineous Marriage and Pathological and Non-pathological Short Stature: A Clinical Investigation - Hameed, Marya; Mahar, Sumera; Sheikh, Fahad Hassan; Siddiqui, Fatima; Khan, Muhammad Khuzzaim; Admani, Bushra (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective To investigate the associations between consanguinity and clinical factors among patients with short stature and to determine whether consanguineous marriage is associated with an increased risk for dysplastic and storage disorders among patients with short stature. Methods This study adopted a retrospective cohort design to investigate common features and potential causes of short stature, specifically focusing on skeletal survey findings. Using a convenience sample of 460 patients, 62% of parents reported consanguineous marriage. The participants were evaluated for clinical factors such as pathological short stature, head size abnormalities, and other related conditions. Data was collected from the medical records of a large tertiary care hospital. Statistical analysis was performed using SPSS 26 software. RESULTS The median age at presentation was 3 years, with a slight skew towards older ages. Males comprised 62.4% of the participants. Notably, 43% of patients had normal short stature, meaning no underlying cause was identified. The remaining patients had pathological short stature caused by various conditions: Metabolic disorders (16.1%), Storage disorders (13.3%), and Dysplastic disorders (18.5%). CONCLUSION The findings suggest that consanguineous marriage is associated with an increased risk for dysplastic and storage disorders. This highlights the need for public health policies and interventions aimed at reducing the prevalence of these conditions in communities where consanguineous marriage is common. Further research is needed to investigate the underlying mechanisms linking consanguineous marriage to health outcomes such as short stature and to develop effective interventions to mitigate the negative impacts of this cultural practice on health.